2006
DOI: 10.1242/jeb.02190
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a branchial epithelial calcium channel (ECaC) in freshwater rainbow trout (Oncorhynchus mykiss)

Abstract: -ATPase-positive (a marker of mitochondria rich cells) cells. Taken together, the results of the present study suggest that although ECaC (mRNA and protein) does exist in trout gill, its cellular distribution is more extensive than previously thought, thus suggesting that Ca 2+ uptake may not be restricted to mitochondria-rich cells as was proposed in previous models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 56 publications
4
39
1
1
Order By: Relevance
“…The cDNA encoding ECaC has been cloned in zebrafish and rainbow trout, and mRNA encoding ECaC was found in a portion of Na + /K + -ATPase-positive MRCs in developing zebrafish (Pan et al, 2005). ECaC immunoreactivity has been found in both pavement cells and Na + /K + -ATPase-positive MRCs of rainbow trout (Shahsavarani et al, 2006). Recently, we have cloned an ECaC homolog from tilapia gills and succeeded in generating a specific antibody showing apical immunoreactivity in gill MRCs (K. M. Lee and T.K., unpublished observations).…”
Section: Is Type I An Immature Mrc?mentioning
confidence: 99%
“…The cDNA encoding ECaC has been cloned in zebrafish and rainbow trout, and mRNA encoding ECaC was found in a portion of Na + /K + -ATPase-positive MRCs in developing zebrafish (Pan et al, 2005). ECaC immunoreactivity has been found in both pavement cells and Na + /K + -ATPase-positive MRCs of rainbow trout (Shahsavarani et al, 2006). Recently, we have cloned an ECaC homolog from tilapia gills and succeeded in generating a specific antibody showing apical immunoreactivity in gill MRCs (K. M. Lee and T.K., unpublished observations).…”
Section: Is Type I An Immature Mrc?mentioning
confidence: 99%
“…Shahsavarani et al, 2006). Samples (50·mg) were size fractionated by reducing SDS-PAGE using 7% separating and 5% stacking polyacrylamide gels and transferred to nitrocellulose membranes (Bio-Rad, Mississanga, ON, Canada).…”
Section: Western Blottingmentioning
confidence: 99%
“…It was undetectable in kidney, intestine, white muscle and blood. A recent study (Shahsavarani et al, 2006) reported that the rainbow trout ECaC was not restricted to mitochondria-rich cells of gills but was also expressed in pavement cells. In the FW zebrafish (Pan et al, 2005), ECaC was ubiquitously expressed in all tissues examined (brain, heart, gills, intestine, liver and kidney); however, expression was highest in the gills and kidney.…”
Section: Tissue-specific Ecac Expressionmentioning
confidence: 97%
“…ECaCs have recently been cloned from rainbow trout (Perry et al, 2003;Shahsavarani et al, 2006), pufferfish (Qiu and Hogstrand, 2004) and zebrafish (Pan et al, 2005). Seemingly there is a single ECaC gene in fish, suggesting that gene duplication occurred after the divergence of fish and mammals (Pan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%